The Role Of Knowledge Innovation In Managing Strategic Momentum (Field Research) - Aref, Ivan Adel; Saeed, Sanaa Abdul Rahim (Journal of Economics and Administrative Sciences, 2020)
The Research Aims To Clarify The Role Of Knowledge Innovation On The Administrative Process Represented by Managing Strategic Momentum, The Research Problem Focuses on Administrative leader Interest In And Implementation Of The Innovation Element Of Knowledge In The Organization By " Managing Strategic Momentum" As Well As The Focus By Management About The Innovators And Makers Of Knowledge And Strategic Planners In The Design And Formulation Of Strategic. Research does Contribute In Solving Part Of The Organizational Problems Of Vision, Innovation And Their Impact On The Momentum Management To Determine The Extent On Which The Procedures Of The Assessed Companies And Plan To Regulate Innovation Under The Momentum Of Strategic Management. The Research Commences from the Main Assumption To Explore The Impact Of The Relationship Between Research Variables And Is Determined By The Field Of Research In Three Leading Iraqi Telecommunication Operators (Asiacell And Korek Telecom And Zain Iraq) Through A Comprised Of Engineers, Experts And Consultants Of (138) As a Purposive Sample Of 103 Individual, And Used Observation And Interview, As Well As The Questionnaire As of Data. Statistical Tools Used for Measurement And Analysis Of The Data Represented by The Coefficient Explorative And Assertive Analysis And The Arithmetic Mean, Standard Deviation And Coefficient Of Variation And The Discovery Of Significant Differences Between The Companies Through Kruskal And Mann Scale Whitney, The Most Prominent Of The Findings Of The Research Are Having A Significant Effect Of Knowledge Creation On The Strategic Momentum Management, The Most Important Conclusions Are The Paramount Importance Of The Process Of Innovation And Continuous Management Of Dynamic Strategic Momentum With Each Step Implementation Of The Strategic Plan, The Most Important Recommendations To Encourage Innovative Courses And Organizational Workshops Strategy To Support The Processes Of Innovation And Progress During The Strategic Administrative System In The Bylaws Of The Companies, Paying Extra Attention To The Senior Management Of The Elements Of Innovative, Strategic And Continuous Support For Its Members.